Effects of different preservation methods on pH, glucose and protein in urine - Tharsikayini, A.; Arasaratnam, V.; Kandeepan, K. (University of Jaffna, 2018)
Delay in transport of urine specimens from collec-tion site to analytical laboratories causes significant errors. Preservatives conserve the characteristics of the urine. The objective of the study was to compare the effect of different preservations on pH, glucose and protein in urine. Collected urine samples from normal individuals were aliquoted for different preservation methods after adding glucose (20, 40, 60, 80, 100 mg/dL) and albumin (20, 30, 100, 300, 500 mg/dL) and stored for 0, 6, 24, 48 and 72 hours. The pH, glucose and protein were measured using pH meter, glucose oxidase, sulfosalicyclic acid methods respectively. Urine samples stored without preservatives showed statistically significant differences (p<0.05) for pH, glucose and protein at 6 hours with 0 hour sample. The pH of urine samples stored at 4°C showed significant differences at 72 hours (p<0.05). Added glucose (20 mg/ dL) and added protein (20 mg/dL) of urine samples stored at 4°C showed significant difference at 24 hours (p<0.05). Urine samples with 40, 60, 80 and 100 mg/ dL ‘added’ glucose and those with 30, 100, 300 and 500 mg/dL ‘added’ protein stored at 4°C showed significant differences at 6 hours (p<0.05). Urine samples stored at 25°C with thymol or toluene showed significant differences at 6 hours (p<0.05) for pH, glucose and protein. Urine samples without preservatives showed significant dif ferences when compared with urine samples at 4°C, either with thymol or toluene (p<0.05). Urine samples stored at 4°C showed significant differences when compared with urine samples either with thymol or toluene (p<0.05). Urine samples with thymol showed no significant differences for pH (p>0.05) while showing significant differences in glucose and protein when compared with urine samples with tolu-ene (p<0.05). The preservation of the urine samples at 4°C is superior to the chemical preservatives and without pre-servatives. If refrigeration is unavailable, then it is recom-mended to use either toluene or thymol. Among the two preservatives, toluene is better to preserve glucose and thy-mol is better to preserve protein. Thymol has strong anti-bacterial attributes whereas toluene acts as a physical bar-rier to air and bacteria.
Keywords: Glucose; pH; Protein; Urine preservatives